Overwhelmed by overflows? How people and organizations create and manage excess - Czarniawska , Barbara (Lund University Press, 2019)
This transdisciplinary volume investigates the ways in which people and organisations deal with the overflow of information, goods or choices. It explores two main themes: the emergence of overflows and the management of overflows, in the sense of either controlling or coping with them. Individual chapters show the management of overflows taking place in various social settings, periods and political contexts. This includes attempts by states to manage future consumption overflow in post-war Easter European, contemporary economies of sharing, managing overflow in health care administration, overflow problems in mass travel and migration, overflow in digital services and the overflow that scholars face in dealing with an abundance of publications.